INNOVATIVE TEACHING APPROACHES TO OVERCOME GRAMMAR DIFFICULTIES IN TRANSLATION - ISOMIDDINOVA, Aziza (The Lingua Spectrum, 2025)
The article explores innovative approaches used to overcome common grammar difficulties in learning and translation. It highlights the effectiveness of task-based learning, digital tools, and interactive activities in improving learners’ grammatical accuracy. The findings show that innovative methods help reduce grammar errors and support learners in achieving clearer and more accurate language competence.